Operating group as a follow-up strategy of a Nursing Course's Pedagogical Project - Gabriella Cristine Guerra de Carvalho; Luciano César Pereira Campos Leonel; Maria Conceição Bernardo de Mello e Souza; Roselma Lucchese; Carla Natalina da Silva Fernandes (Universidade Federal do Ceará, 2014)
The aim of the study was to monitor and describe the implementation process of the Pedagogical Project of the Nursing Undergraduate Course, at the Catalão Campus of the Federal University of Goiás, from the perspective of professors and students. Qualitative and descriptive study, conducted with thirteen participants, of April, 2010 and June, 2011, in Catalão, GO, Brazil. It was possible to use the operative group as a technology for monitoring and data collection. At the end of each meeting, it was possible to set up a chronicle that was subjected to the thematic content analysis. Two categories emerged and showed as potentiality: the curricular matrix interdisciplinarity, and the students' immaturity, the conflictive interpersonal relationship between students and professors as their constraints. Working in small groups and the operative group proved to be assertive in the teaching management and conducting research.